Leadership Academies: A District Office Perspective - Rick Doll (Educational Considerations, 2016)
In 2004, public schools across the country found themselves in the middle of an educational shift to standards-based accreditation. Expectations had changed. Schools were being held accountable for the success of all students. The No Child Left Behind Act of 2001 established the expectation that all schools must successfully educate all students. This federal legislation changed school accreditation to a model based on high-stakes testing.
Keywords: educational; standards-based accreditation. Success; accreditation model; Partnership; relevant curriculum; Kansas superintendent